Suddenly hybrid managing the modern meeting - Reed, Karin M.; Allen, Joseph A. 1981- (Wiley, 2022)
"Prior to COVID 19, hybrid meetings were relatively rare and consisted of the majority of attendees being in person with perhaps someone "dialing in" (and often forgot about). The hybrid meeting that will likely monopolize the way meetings are conducted from here on out will likely involve a group of people gathered in one conference room, maybe another group of people gathered in a huddle room somewhere else, and a variety of folks showing up in their own individual boxes on screen via their personal webcams. Managing the expectations, participation, and conversation flow for all of these different constituencies will be fraught with challenges but perhaps some opportunities as well for the leader who leans into developing new skills. This book provides some much-needed early insight and guidance into what works and what does NOT when it comes to hybrid meetings. Practical, actionable, and implementable steps organizations can take as they adjust and adopt the hybrid model will be provided. These actionable steps will be supported by current research as well as firsthand stories of those who have begun transitioning to this new way of moving business forward. The primary objectives of this book are: To be a science-based but practical guide on managing the hybrid meeting, what will be the "new normal" for the foreseeable future To highlight new research insights gathered from those who are early in the transition To provide actionable best practices based upon the new research, informed by data from the early days of the pandemic, and supported by groups and teams science To illustrate the challenges and opportunities through real-world examples that can allow readers to "walk in the shoes" of those who are making the transition to a hybrid meeting world."--
Includes index
Keywords: Konferenz / (DE-627)091371570 / (DE-2867)19151-5; Arbeitsgruppe / (DE-627)091364698 / (DE-2867)12119-1; Flexibilität / (DE-627)091360463 / (DE-2867)20399-1; Meetings; Flexible work arrangements